Innovations in spatial planning as a social process – phases, actors, conflicts - Gabriela B. Christmann; Oliver Ibert; Johann Jessen; Uwe-Jens Walther (European Planning Studies, 2020)
The aim of this paper is to understand the social process of the emergence and institutionalization of innovations in spatial planning (which we describe as `social innovations'). The paper is based on a recently finished empirical and comparative study conducted in four distinct areas of spatial planning in Germany: urban design, neighbourhood development, urban regeneration and regional planning. The empirical cases selected in these areas encompass different topics, historical periods, degrees of maturity and spatial scales of innovation. As a temporal structure of the innovation processes in the different cases we identified five phases: `incubating, generating, formatting, stabilizing, adjusting'. In a crosscomparison of the case studies and along these phases, we furthermore found typical (groups of) actors, tensions and conflicts. In the focus of our case analyses are the following dimensions: (1) the content of the innovations, (2) actors, networks and communities involved as well as (3) institutions and institutionalization.
Keywords: 710; Social innovations; Conflicts; Urban design; Neighbourhood development; Urban regeneration; Regional planning